PENGARUH KELELAHAN OTOT TERHADAP PERFORMA TENDANGAN MAWASHI GERI PADA ATLET KARATE KOTA SORONG - Istiyono; Agus Kurniadi; Zuli Yanti Rumalean (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The mawashi geri kick is one of the most commonly used attack techniques in karate, especially in kumite numbers. This technique requires strength, speed, balance, and good coordination of the leg muscles so that the kick can be done effectively and accurately. In high-intensity match conditions, athletes often experience muscle fatigue which can affect the quality of technique movements. Muscle fatigue can lead to a decrease in the ability of muscles to produce power, thus having an impact on the speed and power of the kick produced by the athlete. This study aims to determine the effect of muscle fatigue on the performance of mawashi geri kicks in karate athletes in Sorong City. The research method used is a quantitative method with an experimental approach using a one group pretest-posttest design. The research sample amounted to 20 karate athletes who actively trained in several dojos in Sorong City and were selected using purposive sampling techniques. Kick performance measurement is carried out twice, namely before and after athletes are given physical activity aimed at causing muscle fatigue. The research data was obtained through the speed and strength test of the mawashi geri kick. Furthermore, the data was analyzed using a statistical paired sample t-test to find out the difference in kick performance before and after muscle fatigue. The results showed that there was a significant decrease in the speed and strength of the mawashi geri kick after athletes experienced muscle fatigue with a significance value of p < 0.05. Based on the results of the study, it can be concluded that muscle fatigue has a significant effect on the decrease in the performance of mawashi geri kicks in karate athletes in Sorong City. Therefore, coaches need to pay attention to training programs that are able to increase muscle endurance and recovery strategies so that athletes' performance remains optimal during training and matches.